2001
DOI: 10.1006/viro.2001.0980
|View full text |Cite
|
Sign up to set email alerts
|

Infection with Langat Flavivirus or Expression of the Envelope Protein Induces Apoptotic Cell Death

Abstract: Langat (LGT) flavivirus, derived from infectious full-length cDNA clone 636, was investigated for its apoptotic activities in mouse neuroblastoma (Neuro-2a) and simian kidney (Vero and LLC-MK(2)) cells. The hallmark of apoptosis, cleavage of cellular DNA, was observed 48 h after infection of Vero, LLC-MK(2), and Neuro-2a cells by electrophoresis analysis. Apoptosis in infected cells was also confirmed by TUNEL assay. LGT-infected Neuro-2a cells showed an increase in caspase-3-like protease (DEVDase) activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 27 publications
3
33
0
Order By: Relevance
“…Flaviviruses can induce cell death directly through viral replication and the production of proapoptotic proteins (41,43,44,52,57). Notably, pancaspase and caspase 3 inhibitors reduced the WNV-mediated death of primary neurons, which is consistent with studies showing that caspase inhibitors reduced apoptosis after transgenic expression of the flavivirus NS3 and E genes (41,42,44). Caspase-dependent apoptosis of neurons in the CNS may be a general mechanism by which neuroinvasive flaviviruses induce injury.…”
Section: Vol 81 2007 Apoptosis Contributes To West Nile Virus Pathosupporting
confidence: 83%
“…Flaviviruses can induce cell death directly through viral replication and the production of proapoptotic proteins (41,43,44,52,57). Notably, pancaspase and caspase 3 inhibitors reduced the WNV-mediated death of primary neurons, which is consistent with studies showing that caspase inhibitors reduced apoptosis after transgenic expression of the flavivirus NS3 and E genes (41,42,44). Caspase-dependent apoptosis of neurons in the CNS may be a general mechanism by which neuroinvasive flaviviruses induce injury.…”
Section: Vol 81 2007 Apoptosis Contributes To West Nile Virus Pathosupporting
confidence: 83%
“…Recently, we reported that infection with LGT virus or expression of the envelope glycoprotein (E) induces apoptosis through a caspase-3 like protease pathway (25). Here we show that the LGT virus NS3 protein binds to caspase-8 and induces apoptosis.…”
mentioning
confidence: 62%
“…However, apoptosis needs to be delayed long enough for the virus to complete its replication cycle and to produce sufficient quantities of progeny (reviewed in reference 28). Prior experiments showed that infection of Vero and Neuro-2a cells with the LGT virus resulted in release of infectious virus at 24 h in both cell lines, although LGT virus replicates to peak titers in Vero cells that are about 10-fold higher than those in Neuro-2a cells (25). These differences might be important for LGT virus infection in different cell types in vivo but may be less important for cells in culture.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations